Influence of ulexite content on radiation shielding properties of siderite aggregated concretes - Yalim, Huseyin Ali; Ates, Ezgi Yildiz; Uysal, Mucteba (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study evaluates the gamma radiation shielding performance of concretes incorporating varying ratios of siderite and ulexite, with a focus on quantifying the impact of ulexite content on shielding efficiency. Since personnel working in environments such as X-ray facilities and surgical suites are routinely exposed to ionizing radiation, the construction of radiation-shielded spaces is both a legal requirement and a practical necessity. To explore their potential for use in such applications, six concrete mixtures with different siderite-ulexite proportions were prepared in accordance with TSE EN 206+A2 standards. The linear attenuation coefficients (mu) of the samples were experimentally measured using a NaI(Tl)-based gamma spectroscopy system at photon energies of 662, 1173, and 1332 keV (emitted by 137Cs and 60Co sources), and theoretically calculated over the 15 keV to 15 MeV energy range using the Phy-X/PSD code. A strong agreement was observed between the experimental and theoretical mu values. The experimentally determined mu values were subsequently used to calculate the mass attenuation coefficients (MAC). The results demonstrate a clear correlation between the mu values and the siderite/ulexite ratio: increasing siderite content improves shielding effectiveness, while increasing ulexite content reduces it. Overall, concretes containing siderite aggregates exhibit superior gamma-ray shielding performance. Additionally, the Phy-X/PSD code has proven to be an effective tool for predicting the radiation shielding parameters of concrete materials.
Keywords: Gamma-radiation shielding; Attenuation coefficients; Concrete; Siderite; Ulexite; MASS ATTENUATION COEFFICIENTS; EFFECTIVE ATOMIC NUMBERS; GAMMA-RAY; ELECTRON-DENSITIES; BARITE; HEAVY; PARAMETERS; NEUTRON; LEAD; Chemistry; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging